Effect of maturation stage on the physical-chemical composition and bioactive compounds of Solanum granosos-leprosum Dunal fruits (Research, Society and Development, 2020)
The aim of this study was to characterize the capoeira-branca (Solanum granuloso-leprosum Dunal) fruits cultivated in Lavras, Minas Gerais, Brazil. The fruit growth was evaluated, from inflorescence to ripening. For this, measurements were made weekly. The fruits were harvested and separated at three developmental maturation stages (1-immature; 2-green mature; 3-mature), according to the color and size. Then, the fruits were evaluated by size, weight, color, respiration, firmness, pH, titratable acidity, soluble solids, soluble pectin, centesimal composition, vitamin C and antioxidant activity at three stages. During maturation, the fruits showed increase in mass (0.4076 to 0.9956 g), size (7.9 to 12.2 mm), glycidic fraction (15.95 to 27.23%) and ash (0.94 to 1.60%) and reduction in firmness (4.23 to 1.50 kgf), moisture (79.24 to 69.45%) and protein (3.49 to 1.41%) contents. Furthermore, there was increase in soluble solids content (8.80 to 13.80%), antioxidant activity (62.57 to 69.63 μM de trolox.g-1 and 1880.34 to 4602.40 mg.100g-1) and vitamin C (46.81 to 236.02 mg.100g-1) and a decrease in the total phenolics (257.58 to 171.00 mg.100g-1) and soluble pectin (0.92 to 0.69 mg.g-1). The fruits, even after ripening, maintained their greenish color, although less intense than that observed in immature and mature green fruits.